Performansi Turbin Angin Poros Vertikal Tipe Savonius 2 Tingkat Untuk Pengisian Baterai Sebagai Penerangan Lampu Perahu Nelayan Kota Padang - Rizki Muhamad Amsor; R. Iskandar (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
The biggest energy source used today is still predominantly derived from fossil fuels, which is known fossil energy resources are non-renewable so that over time will run out. Therefore, the nowadays conditions should utilize energy sources that are renewable. One of the renewable energy sources that are environmentally friendly and are easy to come is wind energy, which its utilization uses wind turbines. Wind turbines can be used for generating electricity so that it can overcome one of the problems of energy for the fishermen in Padang. Padang has a low to medium wind speeds, so that the suitable wind turbine is Savonius turbine type. The research was done by creating a model of Vertical Axis Wind Turbines (TASV) Savonius type with 2 stages of blades made of aluminum material.  Each rotor is having 50 cm diameter and 80 cm height. Parameter studies that measured are wind speed, rotor rotational speed, turbine force, voltage and current in the generator. Meanwhile, the observation is held on Air Tawar Padang, West Sumatra. From the performance of the Savonius wind turbine in this research is got  5.9 m/s maximum wind speed, 225,8 rpm maximum turbine rotation, 4.7%  the highest Cp and 2 watts the highest power and can catch 160.2 watts the wind power.